2009
DOI: 10.1016/j.bpj.2009.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Location, Structure, and Dynamics of the Synthetic Cannabinoid Ligand CP-55,940 in Lipid Bilayers

Abstract: The widely used hydrophobic cannabinoid ligand CP-55,940 partitions with high efficiency into biomembranes. We studied the location, orientation, and dynamics of CP-55,940 in POPC bilayers by solid-state NMR. Chemical-shift perturbation of POPC protons from the aromatic ring-current effect, as well as 1H NMR cross-relaxation rates, locate the hydroxyphenyl ring of the ligand near the lipid glycerol, carbonyls, and upper acyl-chain methylenes. Order parameters of the hydroxyphenyl ring determined by the 1H-13C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…These studies have shown that the C-3 side chain of classical cannabinoids is aligned parallel with the membrane acyl chains (60,62) and that the fatty acid chain of endogenous cannabinoids orients parallel to membrane acyl chains with terminal methyl near the center of the bilayer (61). Cannabinoid ligand entry at the TMH6/7 interface is supported by isothiocyanate labeling studies of CB2 using the classical cannabinoid, AM841 functionalized at the C-3 dimethylheptyl side chain terminal carbon (1).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These studies have shown that the C-3 side chain of classical cannabinoids is aligned parallel with the membrane acyl chains (60,62) and that the fatty acid chain of endogenous cannabinoids orients parallel to membrane acyl chains with terminal methyl near the center of the bilayer (61). Cannabinoid ligand entry at the TMH6/7 interface is supported by isothiocyanate labeling studies of CB2 using the classical cannabinoid, AM841 functionalized at the C-3 dimethylheptyl side chain terminal carbon (1).…”
Section: Discussionmentioning
confidence: 89%
“…The orientation of both classical and endogenous cannabinoid ligands in the lipid bilayer has been established by small angle x-ray diffraction/differential calorimetry experiments (60), as well as by NMR (61,62). These studies have shown that the C-3 side chain of classical cannabinoids is aligned parallel with the membrane acyl chains (60,62) and that the fatty acid chain of endogenous cannabinoids orients parallel to membrane acyl chains with terminal methyl near the center of the bilayer (61).…”
Section: Discussionmentioning
confidence: 99%
“…CB 2 receptor is activated upon specific binding of cannabinoid agonists to a putative binding site formed by transmembrane helices III, V, VI, and VII near the extracellular membrane surface (21,45). Current models propose that ligand binding induces a conformational change in CB 2 receptor, resulting in formation of a catalytic surface on the cytoplasmic side of the receptor where binding and activation of cognate G proteins takes place.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the more hydrophobic CP55940 would have a slower apparent rate of repartitioning from an empty micelle to a micelle containing a receptor, and this could thus contribute to the slower observed fluorescence change/conformational change in the labeled CB1. Similarly, the faster rate of change observed for the antagonist SR141716A might be partially due to its greater aqueous solubility (lower octanol/water partition coefficient when compared with agonist -1 ϫ 10 5 versus 1.6 ϫ 10 6 , respectively) (45,46). Notably, multistep binding models have previously been proposed for cannabinoid ligands to account for their interaction with membranes (47,48).…”
Section: Discussionmentioning
confidence: 99%